PROFESSIONAL COMMITMENT TO SOCIETY: A REPORT OF A SOCIAL INTERVENTION BY ACADEMICS IN A BRAZILIAN SMALL TOWN - Pasqualini, Juliana Campregher [UNESP]; Martins, Fernando Ramalho [UNESP]; Miguel, Roberto Carlos [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This paper aims to report the experience of a group composed by two assistant professors and eight students from UNESP in a multidisciplinary social project, realized in July, 2015 in a small town from Mato Grosso State. The team was formed by students from the following areas: public management, biology, pharmacy, education, psychology, and social service. We are going to describe here the process of preparation, planning and execution of the actions developed by the team, stressing the main results, the difficulties faced by the students, and how this experience has added to them in terms of their professional improvement. Two aspects will be highlighted as primary in the achievement of our goals: the group process and social policies as guiding principles of the actions developed.
Keywords: Social project; Skill building; Group process; Social policies; Projeto Rondon